2016
DOI: 10.1590/s0080-623420160000400008
|View full text |Cite
|
Sign up to set email alerts
|

Triage in an adult emergency service: patient satisfaction

Abstract: Objective: Assess the degree of patient satisfaction with triage in the adult emergency service of a public hospital. Method: Exploratory, descriptive, cross-sectional study with a quantitative approach. Three hundred patients were interviewed and the data were analyzed using descriptive statistics based on sociodemographic variables and those related to patient satisfaction. Results: There was a predominance of women, with elementary education and a mean age of 41 years. Most of the interviewees reported bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
25

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 20 publications
0
18
0
25
Order By: Relevance
“…it is explicit in the article, in the Method, that this study focused on sociodemographic variables (gender, age, education and medical specialty) and variables related to patient satisfaction, which were already mentioned in the study objective. Overcrowding is a worldwide phenomenon (1)(2)(3)(4) in emergency medical services and, nonetheless, the results in these studies demonstrated satisfaction. Provided that the higher the level of education the greater the patient's criticism regarding the services delivered, a limitation of this study consisted of the data that indicate subjects' precarious education and income, since their level of satisfaction may be related to the low level of quality demanded from public health services by these subjects.…”
Section: As Regards the Question: "The Main Focus Of Emergency Departmentioning
confidence: 70%
See 1 more Smart Citation
“…it is explicit in the article, in the Method, that this study focused on sociodemographic variables (gender, age, education and medical specialty) and variables related to patient satisfaction, which were already mentioned in the study objective. Overcrowding is a worldwide phenomenon (1)(2)(3)(4) in emergency medical services and, nonetheless, the results in these studies demonstrated satisfaction. Provided that the higher the level of education the greater the patient's criticism regarding the services delivered, a limitation of this study consisted of the data that indicate subjects' precarious education and income, since their level of satisfaction may be related to the low level of quality demanded from public health services by these subjects.…”
Section: As Regards the Question: "The Main Focus Of Emergency Departmentioning
confidence: 70%
“…I have read the outstanding publication in the Rev Esc Enferm USP Journal from Silva et al entitled "Triage in an adult emergency service: patient satisfaction" (1) . The authors concluded that there was a high level of patient satisfaction.…”
mentioning
confidence: 99%
“…Nesse sentido, pontuase o fato de ter havido predomínio de participantes com baixo nível socioeconômico no presente estudo, uma vez que dados observados em pesquisas similares indicam que este é um fator que influencia na avaliação da satisfação de usuários de instituições de saúde 10,25 .…”
Section: Discussionunclassified
“…Pontua-se que, de acordo com a resolução nº 423/2012 do Conselho Federal de Enfermagem, a classificação de risco e a priorização da assistência em serviços de urgência é privativa do enfermeiro, observadas as disposições legais da profissão 9 . É importante destacar que a realização dessa classificação não é uma atividade tão simples quanto parece, uma vez que depende tanto das habilidades e competências profissionais dos enfermeiros como também de fatores externos e subjetivos relacionados ao atendimento, tais como o ambiente de trabalho, o relacionamento interpessoal e a comunicação estabelecida entre profissional e paciente 10 . Isso justifica a necessidade de se realizar capacitações dos profissionais responsáveis pela classificação, pois em um estudo nacional foi evidenciado que, quanto maior a qualificação do profissional, mais assertivas são as classificações de risco atribuídas por ele 11 .…”
unclassified
“…Aunque no se converge completamente en las dimensiones o atributos que producen más satisfacción a los pacientes -ya que depende del servicio que se analice-, la literatura señala que son los aspectos relacionados con la empatía los citados con mayor frecuencia. En el análisis de la satisfacción o insatisfacción del paciente con los servicios de urgencias, hay cierto consenso acerca de los factores determinantes de la percepción de calidad de los pacientes respecto al trato, los tiempos de espera y las instalaciones (21).…”
Section: Fundamentos Teóricosunclassified